2011
DOI: 10.1161/strokeaha.110.606889
|View full text |Cite
|
Sign up to set email alerts
|

A Cost–Utility Analysis of Mechanical Thrombectomy as an Adjunct to Intravenous Tissue-Type Plasminogen Activator for Acute Large-Vessel Ischemic Stroke

Abstract: Background and Purpose-Mechanical thrombectomy has the potential to improve recanalization rates and outcomes for patients with ischemic stroke, but potential gains could be offset by procedural complications and costs. We evaluated the cost and utility of combined intravenous (IV) tissue-type plasminogen activator (tPA) and mechanical thrombectomy compared to IV tPA alone for acute large-vessel ischemic stroke. Methods-We constructed a decision tree for a hypothetical 68-year-old with a large-vessel ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Considering clinical and financial recently reported data [20][21][22] , we can argue that it would be logical to perform the endovascular treatment of AIS in regional hospital centres with a stroke unit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering clinical and financial recently reported data [20][21][22] , we can argue that it would be logical to perform the endovascular treatment of AIS in regional hospital centres with a stroke unit.…”
Section: Resultsmentioning
confidence: 99%
“…Cost-effectiveness studies concerning primary 4 and secondary prevention 5 , diagnostic testing 6 , thrombolysis [7][8][9][10][11][12][13][14][15] , rehabilitation 16 , management systems 17 and also the informal care costs of long-term care after stroke 18,19 have been published. Few studies have explored the cost-effectiveness of mechanical thrombectomy [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the available data, mechanical therapies in qualified patients with acute stroke beyond the window for IV tPA [15] and the combination of IV tPA and mechanical thrombectomy for large-vessel ischemic stroke appears to be cost-effective [16]. Even though mechanical thrombectomy is usually offered later in the course of acute stroke when revascularization is generally less effective, a sensitivity analysis based on the results of the MERCI study [17] showed that, although mechanical thrombectomy carries an approximately USD 6,600 higher cost compared with standard medical therapy, it remained cost-effective [18].…”
Section: Discussionmentioning
confidence: 99%
“…Email: jankbt@upmc.edu be increased and mortality rates reduced [13,14]. Furthermore, these procedures have been shown to be costeffective [15,16]. While this represents an improvement over intravenous tPA, the procedures take a significant amount of time and recanalization rates remain mediocre.…”
Section: Introductionmentioning
confidence: 99%